Normal development and function of T cells in proline rich 7 (Prr7) deficient mice - Hrdinka, M; Sudan, K; Just, S; Drobek, A; Stepanek, O; Schlüter, D; Reinhold, D; Jordan, B; Gintschel, P; Schraven, B; Kreutz, M (Public Library of Science, 2016)
Transmembrane adaptor proteins (TRAPs) are important organisers for the transduction of immunoreceptor-mediated signals. Prr7 is a TRAP that regulates T cell receptor (TCR) signalling and potently induces cell death when overexpressed in human Jurkat T cells. Whether endogenous Prr7 has a similar functional role is currently unknown. To address this issue, we analysed the development and function of the immune system in Prr7 knockout mice. We found that loss of Prr7 partially impairs development of single positive CD4+ T cells in the thymus but has no effect on the development of other T cell subpopulations, B cells, NK cells, or NKT cells. Moreover, Prr7 does not affect the TCR signalling pathway as T cells derived from Prr7 knockout and wild-type animals and stimulated in vitro express the same levels of the activation marker CD69, and retain their ability to proliferate and activate induced cell death programs. Importantly, Prr7 knockout mice retained the capacity to mount a protective immune response when challenged with Listeria monocytogenes infection in vivo. In addition, T cell effector functions (activation, migration, and reactivation) were normal following induction of experimental autoimmune encephalomyelitis (EAE) in Prr7 knockout mice. Collectively, our work shows that loss of Prr7 does not result in a major immune system phenotype and suggests that Prr7 has a dispensable function for TCR signalling.